MSMEs HR Understanding on Copyright Protection of Creative Works Digital Marketing Social Media Platforms in The Digital Era (Study on SMEs assisted by Kadin City of Bandung) - Nina Nurani; Nurul Hermina; Erwin Firdaus (Universitas Mercu Buana, 2023)
Objectives: The human resources and individuals in MSMEs must have a comprehensive understanding of the importance of copyright protection which has been regulated in Law No. 28 of 2014 for assuring the existence of fair market and trade. This study aims to find out how the understanding of MSMEs HR towards copyright protection for digital creative works in social media platforms in the digital era. Methodology: This study uses descriptive qualitative analysis and normative juridical analysis to assess the phenomenon that occurs in human resources in MSMEs. The data used is cross-sectional data from 40 MSMEs in Bandung, combined with legal interpretation and construction methods.Finding: The results indicate that 26% of MSMEs in Bandung City still do not understand the meaning and importance of creative digital marketing work as an asset. They need to get copyright protection as an exclusive right through registration. It also indicates that 14.7 % of MSMEs do not understand the consequence of digital content marketing copyrighted works if it gets commercialized as it provides royalty benefits. This finding implies and encourages more creative and innovative works for digital marketing in social media platforms for MSMEs to obtain business competitiveness in the digital era.Conclusion: A comprehensive understanding of the importance of copyright protection for creative digital works through registration is crucial. The active role of the government is needed to educate MSMEs. This study recommends that future studies can be done using a quantitative verificative method by adding and considering other variables such as MSME's performance and organizational culture.